2001
DOI: 10.1007/s007050170011
|View full text |Cite
|
Sign up to set email alerts
|

Cross-protection studies between respiratory and calf diarrhea and winter dysentery coronavirus strains in calves and RT-PCR and nested PCR for their detection

Abstract: A 1-step RT-PCR assay, targeting a 730 bp fragment of the nucleocapsid (N) gene of bovine coronavirus (BCV), and a nested PCR assay, targeting a 407 bp fragment of the N gene, were developed to detect BCV in nasal swab and fecal samples of calves experimentally exposed to BCV. Both 1-step RT-PCR and nested PCR recognized cell culture passaged isolates of 10 bovine respiratory coronavirus (BRCV), 5 calf diarrhea (CD) and 8 winter dysentery (WD) strains of BCV, but not transmissible gastroenteritis coronavirus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
139
0
8

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(158 citation statements)
references
References 23 publications
3
139
0
8
Order By: Relevance
“…Electron microscopic examination and an indirect antigen-capture ELISA employing monoclonal antibodies to BoCV as capture antibodies were used to detect BoCV in the fecal samples as previously described [2,[9][10][11]13]. To detect the BoCV-RNA, RT-PCR and nested PCR with specific primer pairs were performed with the extracted RNA from fecal samples as described by Cho et al [4]. As a negative control, RNA was extracted from mock-infected human rectal tumor (HRT-18G) cells or mock-infected bovine fecal samples.…”
mentioning
confidence: 99%
“…Electron microscopic examination and an indirect antigen-capture ELISA employing monoclonal antibodies to BoCV as capture antibodies were used to detect BoCV in the fecal samples as previously described [2,[9][10][11]13]. To detect the BoCV-RNA, RT-PCR and nested PCR with specific primer pairs were performed with the extracted RNA from fecal samples as described by Cho et al [4]. As a negative control, RNA was extracted from mock-infected human rectal tumor (HRT-18G) cells or mock-infected bovine fecal samples.…”
mentioning
confidence: 99%
“…Such dissimilarity may be due to the genomic region chosen as the target of the coding region of HE protein, which presents a higher diversity if compared to the coding region of N protein, a highly conserved region 22 , targeted by the authors of the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…It indicated that the sensitivity of duplex RT-PCR was same with single PCR. Compared with the reported RT-PCR methods [5,6,10,11], our method appears to be sensitive enough for the detection of clinical samples.…”
mentioning
confidence: 99%